2013
DOI: 10.1002/jgra.50362
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary and geomagnetic consequences of 5 January 2005 CMEs associated with eruptive filaments

Abstract: , SoHO/LASCO observed the launch of two successive coronal mass ejections (CMEs) associated with the filament (active region and quiescent) structures. The eruptions resulted in two distinct magnetic clouds whose embedded flux-rope topology is modeled by the Grad-Shafranov (G-S) reconstruction technique. Filament plasma remnants in these magnetic clouds were identified using a combination of in situ plasma, magnetic, and composition signatures. In situ spacecraft (ACE and Wind) measurements suggest interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…Here we have to remind that the solar wind plasma of very high density was originated from an erupting filament [Foullon et al, 2007], which usually contains a significant portion of He. Sharma et al [2013] reported very large He to proton ratio of >20% in the filament plasma observed by ACE/Solar Wind Ion Composition Spectrometer on 7-8 January 2005. It is important to note that those days were not accompanied either by enhanced SEP fluxes or by very fast solar wind and, hence, the Composition Aperture telescope onboard ACE was operating safely.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Here we have to remind that the solar wind plasma of very high density was originated from an erupting filament [Foullon et al, 2007], which usually contains a significant portion of He. Sharma et al [2013] reported very large He to proton ratio of >20% in the filament plasma observed by ACE/Solar Wind Ion Composition Spectrometer on 7-8 January 2005. It is important to note that those days were not accompanied either by enhanced SEP fluxes or by very fast solar wind and, hence, the Composition Aperture telescope onboard ACE was operating safely.…”
Section: Discussionmentioning
confidence: 94%
“…Sharma et al . [] reported very large He to proton ratio of >20% in the filament plasma observed by ACE/Solar Wind Ion Composition Spectrometer on 7–8 January 2005. It is important to note that those days were not accompanied either by enhanced SEP fluxes or by very fast solar wind and, hence, the Composition Aperture telescope onboard ACE was operating safely.…”
Section: Discussionmentioning
confidence: 99%
“…All the significant filaments identified to date have been different in their charge-state composition and in the distribution of cold filament material within and surrounding the ICME [cf. Burlaga et al, 1998;Skoug et al, 1999;Farrugia et al, 2002;Lepri and Zurbuchen, 2010;Sharma et al, 2013] suggesting that complex processes are responsible for their transport to 1 AU.…”
Section: Introductionmentioning
confidence: 99%
“…3D rendering of associated plasma structures is done by the use of time dependent reconstruction algorithm (Jackson et al, 2002, and references therein). Sharma et al (2013) reported the event by the study of remote and in-situ observations of two CMEs associated with an active region and quiescent filaments on 5 January 2005. The first CME was associated with an east -west oriented filament and was slow in velocity and acceleration as compared to the second north -south oriented filament.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…At their interface region, these magnetic clouds have embedded filament plasma that shows complex magnetic structures with a distinct magnetic flux rope configuration; these have been modeled by the Grad -Shafranov reconstruction technique. The geomagnetic consequences of these structures have been associated with substorms in recovery phase of a storm and detailed analysis is presented in Sharma et al (2013). In the present paper, we highlight the comparison of shape and extent of two filament plasma remnants in magnetic clouds as revealed by three -dimensional (3D) reconstruction and analysis from the Solar Mass Ejection Imager (SMEI) data.…”
mentioning
confidence: 98%